Systematic review and meta-analysis of local resection or transanal endoscopic microsurgery versus radical resection in stage i rectal cancer: A real standard?. (June 2017) - Veereman, Geneviève; Vlayen, Joan; Robays, Jo; Fairon, Nicolas; Stordeur, Sabine; Rolfo, Christian; Bielen, Didier; Bols, Alain; Demetter, Pieter; D'hoore, André; Haustermans, Karin; Hendlisz, Alain; et al.
Abstract: Current guidelines recommend radical resection for stage I rectal cancer. However, since screening programs are being installed, an increasing number of cancers are being detected in early stages. Endoscopic resection is often performed at the time of diagnosis. This systematic review was undertaken to review the evidence on endoscopic approach vs. radical resection for stage I rectal cancer. Recommendations were issued based on the GRADE methodology and risk stratification used in clinical practice. A systematic search (until March 2015) identified 2 meta-analyses and 1 additional randomized trial. For the primary outcomes (overall survival, disease-free survival, local recurrence-free survival and metastasis-free survival) no evidence could be found on the superiority of local or radical resection. Secondary outcomes (blood loss, hospital stay, operative time, number of permanent stomas and perioperative deaths) were in favour of local resection. The authors strongly recommend radical resection for T2 rectal cancer, but consider 'en bloc' local resection sufficient for pT1 sm1 rectal cancers when confirmed pathologically. Discussion by a multidisciplinary team and adequate surveillance remain mandatory.